SAMPLING BACTERIAL BIODIVERSITY FROM A HIGHLY CONTAMINATED STREAM FLOWING THROUGH A DENSELY POPULATED URBAN AREA IN KARACHI - Enam, Syed Faaiz; Qureshi, Humaira; Qureshi, Sohail A. (Journal of Ayub Medical College Abbottabad, 2011)
Background: Few studies have attempted to understand the complexity of microbial populations in Pakistan where infectious diseases are prevalent. This study was undertaken to assess bacterial biodiversity in Nehr-e-Khayyam a heavily polluted stream connected to the Arabian Gulf, which runs through a densely populated urban area in Karachi, Pakistan. Methods: Employing a universal pair of oligonucleotides capable of amplifying species-specific segments of 16S rRNA gene from all Eubacteria, we generated a library of PCR products using total DNA purified from the collected sample, cloned the amplifers into pGEM-T-Easy and sequenced each recombinant clone. The obtained DNA sequences were subjected to bio-informatic analyses. Results: A total of 71 recombinant clones were obtained from the amplified 16S rDNA products and sequenced. Bioinformatics analyses revealed that 54 (out of 71) were unique sequences from which 42 shared >97% and 12 shared <97% homology to their database counterparts. One sequence originated from the plastid DNA of eukaryote Pyramimonas disomata. From the remaining 53 sequences, 45 were Proteo-bacteria and 8 Fermicute in origin. Among 71 sequences, Alpha-, Beta- and Gamma-proteobacteria species constituted 86% of Proteo-bacteria identified in the sample while only 13% were Fermicutes. Conclusions: The microbial niche in Nehr-e-Khayyam is occupied predominantly by heterotrophic Proteo-bacterial and Firmicute strains, some of which are known human pathogens. Keywords: Bacteria, biodiversity, 16S rDNA, Karachi